REPRESENTASI LOYALITAS YANG TERKANDUNG DALAM MUSIC VIDEO BTS “WE ARE BULLETPROOF: THE ETERNAL” - Kamelia Hanashofi Asih; Muhammad Adi Sukma Nalendra (Puslitabmas Batam Tourism Polytecnic, 2022)
This research is about the meaning of visualization in the music video